2014
DOI: 10.1002/bmc.3295
|View full text |Cite
|
Sign up to set email alerts
|

Automatic analyzer for highly polar carboxylic acids based on fluorescence derivatization–liquid chromatography

Abstract: A sensitive, versatile, and reproducible automatic analyzer for highly polar carboxylic acids based on a fluorescence derivatization-liquid chromatography (LC) method was developed. In this method, carboxylic acids were automatically and fluorescently derivatized with 4-(N,N-dimethylaminosulfonyl)-7-piperazino-2,1,3-benzoxadiazole (DBD-PZ) in the presence of 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride by adopting a pretreatment program installed in an LC autosampler. All of the DBD-PZ-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, artificial intelligence (AI) technology including deep learning (DL) has resulted in remarkable progress in medicine, and various applications for diagnostic imaging have been reported 15 . In the field of ophthalmology, many researchers, including the authors, have reported the performance of DL in image analysis using in vivo laser confocal microscopy, optical coherence tomography (OCT), OCT angiography, and ultra-wide-field fundus ophthalmoscopy 16 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial intelligence (AI) technology including deep learning (DL) has resulted in remarkable progress in medicine, and various applications for diagnostic imaging have been reported 15 . In the field of ophthalmology, many researchers, including the authors, have reported the performance of DL in image analysis using in vivo laser confocal microscopy, optical coherence tomography (OCT), OCT angiography, and ultra-wide-field fundus ophthalmoscopy 16 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, artificial intelligence (AI) technologies, including deep learning (DL), have made remarkable progress and, in the medical field, various applications in diagnostic imaging have been reported [22]. In the field of ophthalmology, many researchers, including the authors, have already reported applications of DL to image analysis using OCT, OCT angiography, and ultrawide-field fundus ophthalmoscopy [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%